Practical use and development of biomérieux TEMPO® system in microbial food safety - Alsaadi, Yousef Saeed (Kansas State University, 2014)
In the food industry, coliform testing is traditionally done by the time consuming and labor intensive plate count method or tube enumeration methods. The TEMPO® system (bioMérieux, Inc.) was developed to improve laboratory efficiency and to replace traditional methods. It uses a miniaturization of the Most Probable Number (MPN) method with 16 tubes with 3 dilutions in one single disposable card. It utilizes two stations: the TEMPO® Preparation station and the TEMPO® Reading station. In this study, the Oxyase® (Oxyase®, Inc.) enzyme was added to TEMPO® CC (Coliforms Count), TEMPO® AC (aerobic colony count) and TEMPO® EC (E. coli Count) methods. Water samples of 1 ml with 0.1 ml of Oxyase® enzyme were compared to samples without the Oxyase® enzyme using the TEMPO® system. Samples were spiked with different levels of coliforms (10, 102, 103 and 104 CFU/ml), stomached (20 sec), and pipetted into the three different TEMPO® media reagents (4 ml) in duplicate and then automatically transferred into the corresponding TEMPO® cards by the TEMPO® preparation station. Counts were obtained using the TEMPO® reading station after 8, 12, 16, 22 and 24 hours at an incubation temperature of 35°C. Results from 20 replicates were compared statistically. Using TEMPO® tests, high counts in food samples (>6 log 10 CFU/ml) can be read in 6±2 hours of incubation using the time-to-detection calibration curve. The TEMPO® system reduces reading time (reading protocol should be changed). There is no need to wait for 22 hours of incubation only 12 hours is required. Oxyrase® enzyme is not needed for the TEMPO® system.
Keywords: Oxyase® enzyme; TEMPO®; Indicator organisms; BbioMérieux; Aerobic colony count; E. coli Count; Coliforms count; Food Science (0359); Microbiology (0410)